Otoritas dan Pola Pengawasan Perbankan Syariah di Indonesia - Bagya Agung Prabowo (Fakultas Hukum Universitas Islam Indonesia, 2003)
The monetary crisis in Indonesia has shown that the syariah banking proves that it has the significant endurance. For law protection interest for customers, syariah banking need thesupervision authority for two both aspects. The first is banking administrative supervision, and the second is the syariah supervision. This task is actually takenby the institution of authority consent of supervision (Bl or OJK), because the effectiveness of syariah depends greatly on the sanction available. Through single supervision pattern, the dualism of guidance and counseling for banking in Indonesia is deni able. The syariah protection for the customers can as well as be taken by optimalization of the National Syariah Board and Syariah Supervision Board.